Comparing the effects of muscle energy technique and mulligan mobilization with movements on pain, range of motion, and disability in adhesive capsulitis - Razzaq, Ayesha; Nadeem, Rana Dilawaiz; Muhammad Akhtar; Ghazanfar, Mariam; Aslam, Naeem; Nawaz, Sadia (Journal of the Pakistan Medical Association, 2022)
Objective: To compare the effect of muscle energy technique and Mulligan mobilisation with movement on pain, range of motion and disability in patients of adhesive capsulitis. Methods: The single-blind, randomised controlled study was conducted at the Physiotherapy Department of Mayo Hospital, Lahore, Pakistan, from July to December, 2018, and comprised patients of either gender aged 30-70 years with adhesive capsulitis stage 2. The subjects were randomised using the lottery method into Mulligan mobilisation with movement group A, and the muscle energy technique grouo B. Conventional treatment, including hot packs and exercises like pulley rope exercise, wall climbing, and shoulder wheel, were part of both the groups. Each technique was applied five times per set, 2 sets per session 3 days a week for three weeks. Baseline and post-intervention readings were recorded for pain, range of motion and disability Using numeric pain rating scale, goniometer, and shoulder pain and disability index. Data was analysed using SPSS 23. Results: Of the 70 individuals assessed, 64(91.4%) were included; 32(50%) in each of the two groups. The mean age in group A was 49.93±6.69 years, while in group B it was 49.17±8.92 years. Group A showed significantly better result compared to group B (p<0.05). Conclusion: Muscle energy technique and Mulligan mobilisation with movement were both found to be effective, but the latter was significantly better compared to the former. Clinical Trial Number: IRCT20200611047734N2 (https://www.irct.ir/trial/48851) Continuous...